Access to primary health care for immigrants: results of a patient survey conducted in 137 primary care practices in Ontario, Canada - Muggah Elizabeth; Dahrouge Simone; Hogg William (BMC Family Practice, 2012)
Abstract Background Immigrants make up one fifth of the Canadian population and this number continues to grow. Adequate access to primary health care is important for this population but it is not clear if this is being achieved. This study explored patient reported access to primary health care of a population of immigrants in Ontario, Canada who were users of the primary care system and compared this with Canadian-born individuals; and by model of primary care practice. Methods This study uses data from the Comparison of Models of Primary Care Study (COMP-PC), a mixed-methods, practice-based, cross-sectional study that collected information from patients and providers in 137 primary care practices across Ontario, Canada in 2005-2006. The practices were randomly sampled to ensure an equal number of practices in each of the four dominant primary care models at that time: Fee-For-Service, Community Health Centres, and the two main capitation models (Health Service Organization and Family Health Networks). Adult patients of participating practices were identified when they presented for an appointment and completed a survey in the waiting room. Three measures of access were used, all derived from the patient survey: First Contact Access, First Contact Utilization (both based on the Primary Care Assessment Tool) and number of self-reported visits to the practice in the past year. Results Of the 5,269 patients who reported country of birth 1,099 (20.8%) were born outside of Canada. In adjusted analysis, recent immigrants (arrival in Canada within the past five years) and immigrants in Canada for more than 20 years were less likely to report good health compared to Canadian-born (Odds ratio 0.58, 95% CI 0.36,0.92 and 0.81, 95% CI 0.67,0.99). Overall, immigrants reported equal access to primary care services compared with Canadian-born. Within immigrant groups recently arrived immigrants had similar access scores to Canadian-born but reported 5.3 more primary care visits after adjusting for health status. Looking across models, recent immigrants in Fee-For-Service practices reported poorer access and fewer primary care visits compared to Canadian-born. Conclusions Overall, immigrants who were users of the primary care system reported a similar level of access as Canadian-born individuals. While recent immigrants are in poorer health compared with Canadian-born they report adequate access to primary care. The differences in access for recently arrived immigrants, across primary care models suggests that organizational features of primary care may lead to inequity in access.